Material events : Paul de Man and the afterlife of theory - Cohen, Tom, 1953- (University of Minnesota Press, 2001)
Responding to the problematic of "materialism" as posed in Paul de Mans posthumous last book, Aesthetic Ideology, a diverse and distinguished group of scholars explores the question of "material events" in ways that illuminate not just de Mans work but their own, work at the forefront of critical theory, productive thinking, and writing in the humanities.